ESTUDIO DEL CLIMA LABORAL DE LOS SERVIDORES DEL CENTRO DE APOYO SOCIAL MUNICIPAL DE LOJA (CASMUL), AÑO 2024. - Sánchez Carrillo, Kevin Julián (2025)
The present study evaluates the work climate at the Centro de Apoyo Social Municipal de Loja (CASMUL), to identify its current state, examine the factors that affect it, and suggest improvement strategies. The methodology used includes a survey structured by the authors Litwin and Stringer with 53 questions that evaluate 9 dimensions such as structure, responsibility, rewards, risks, relationships, support, norms, conflicts, and identity; in addition, an unstructured observation sheet and semi-structured interviews based on Elton Mayo were used with key staff members. The results indicate that the work environment is acceptable, with an average of 65%, although there are areas that need attention, particularly in the dimensions of reward, relationships, and conflict, where the averages are below 2.51. A lack of assumption of responsibility and a negative environment in terms of rewards have been identified, which has a negative impact on motivation and collaboration among employees. Likewise, the importance of communication and trust in the work environment is highlighted. The conclusions suggest the implementation of improvement strategies in the dimensions with low averages to promote a more positive and productive work environment. An employee recognition system and improvements in communication between management and staff are recommended as opportunities to strengthen the work environment. This analysis is essential to ensure better service to the community and to increase the satisfaction and performance of CASMUL employees.